Synthesis, characterization and structures-property investigations on a series of carbazole thiophene derivatives / Emmy Fadhiza Damit - Emmy Fadhiza , Damit (2016)
The main objective of the present research is to investigate structure property of a series of carbazole-thiophene. Electronic properties were evaluated by UV-Vis, cyclic voltammogram and theoretical calculations. Particularly, the effects of conjugation connectivity on photophysical and electrochemical properties, as well as the correlation between carbazole-thiophene were linked at the N-9 position for different core groups via biphenyl, dimethylbiphenyl and phenyl were studied. Literature review on the carbazole-thiophene moieties and their derivatives and methods for the synthesis of carbazole-thiophene have been described. The literature search on the various potential application of carbazole-thiophene were also studied. A brief introduction on the background of this study was provided which gave an insight of the key step involved in the synthesis of carbazole-thiophenes via Suzuki Miyaura and Ullmann coupling reaction. Results of the physical properties on the electronic absorption spectroscopy via UV-visible and fluorescence were discussed. We noted a maximum absorption wavelength at a higher absorbance, indicating that the attachment of thiophene groups at the 3- and 6-positions of the carbazole significantly enhances the optical properties. The absorption bands of all of the compounds were gradually red shifted, when the thiophene group was connected to the carbazole at the 3- and 6- positions and the extent of π-conjugation in the compounds increased, as expected. After the functionalization of the carbazole groups, the fluorescence maxima (λem) gradually red shifted upon the addition of thiophene group, resulting a significant red shift in the emission spectrum. Epa values for 2.38 (P1), 2.39 (P2), 2.40 (P3), 2.41 (P4), 2.42 (P5), 2.43 (P6), 2.44 (P7), 2.45 (P8), 2.46 (P9) and 2.47 (P10) are cathodically shifted compared to those for 1.4 (CBP), 2.36 (CDBP), 2.37 (BCP) by the subsequent addition of thiophene molecules, demonstrating that the connection with thiophene at the 3- and 6-positions on carbazole of 1.4 (CBP), 2.36 (CDBP) and 2.37 (BCP) gives rise to high electrochemical stability and effectively enhances donor ability. Carbazole substituted with thiophene groups at the 3- and 6-positions leads to greater stabilization of HOMO and LUMO energy levels where the band gap (ΔE) of all the compounds is significantly reduced and such unit can be introduced into the backbone of 1.4 (CBP), 2.36 (CDBP) and 2.37 (BCP) π-conjugated small molecules to develop new materials with low band gap that may have potential application in optoelectronic fields. A brief introduction of theoretical calculation was provided. A brief theoretical calculation on the carbazole-thiophenes compounds by geometrical optimization and frontier molecular orbital calculations were also discussed. All computation were performed using GAUSSION 09W software package employing the Density Functional Theory (DFT) method with correlation functional B3LYP and 6-31G as functional basis set.